The impact of technological advancement on culture and society - Abdullah Alsaleh (Scientific Reports, 2024)
Abstract Technology plays a pivotal role in shaping cultural identities and practices across the globe. This paper explores the complex relationship between technology and cultural transformation, recognizing both its opportunities and challenges in diverse cultural contexts. We employ key theoretical frameworks, including cultural diffusion, technological determinism and the digital divide, to examine how technological advancements contribute to cultural development. Our findings reveal that technology acts as a catalyst for cultural exchange, innovation and adaptation, enabling unprecedented global communication and the exchange of ideas. For example, the rapid spread of the internet and mobile technologies has facilitated cross-cultural interactions, leading to the blending of cultural values and practices on a global scale. However, the research also highlights the challenges posed by technology, such as the digital divide, which exacerbates inequalities in access to digital resources, and the risk of cultural homogenization, where dominant global cultures overshadow local identities. This study underscores the dual nature of technological influence: while it fosters cultural enrichment and connectivity, it also poses risks to cultural diversity and equity. By analyzing empirical case studies, we show how these dynamics unfold in real-world contexts. Ultimately, this paper advocates for inclusive, mindful approaches to technological integration that respect and preserve cultural diversity. Our findings offer valuable insights for policymakers, educators and technologists, emphasizing the need for culturally sensitive strategies to ensure that technological progress enhances, rather than erodes, cultural heritage in the digital age.